RELATIONSHIP BETWEEN SOIL-TRANSMITTED HELMINTHS (STH) EGG CONTAMINATION IN YARD SOIL TO HELMINTHIASIS INFECTION IN CHILDREN ELEMENTARY SCHOOL IN GAMPONG JAWA KUTA RAJA SUB-DISTRICT BANDA ACEH CITY - Rahmayanti Rahmayanti; Siti Hadijah; Erlinawati Erlinawati (Universitas Islam Negeri Ar-Raniry, 2023)
Soil-Transmitted Helminths (STH) are a type of intestinal worm that infects humans through soil contaminated with parasitic worms such as roundworms (Ascaris lumbricoides), whipworms (Trichuris trichiura), and hookworms (Ancylostoma duodenale and Necator americanus). STH infections have detrimental effects on children, which can be worrisome for their survival as well as their mental and physical development. Soil is one of the intermediaries for helminthiasis infection because surface soil is a place where worm eggs can survive for a long time. Feces from people with helminthiasis are an important source of soil contamination. This study is an analytical observational study with a cross-sectional design and purposive sampling technique with 50 elementary school-aged children in Gampong Jawa, Kuta Raja District, Banda Aceh City. Examination of the incidence of worms in children is done by examining feces (Kato-Katz method). The examination of soil samples using the floatation method. The results of the soil examination in this study showed that the soil in the children's yard was polluted by STH eggs by 26% and the soil that was not polluted by STH eggs by 74%. The highest STH contamination was Ascaris lumbricoides eggs at 43.5%. The results of fecal examination in children showed that as many as 10 people (20%) were infected with STH and 40 people (80%) were not infected with STH. Based on the Chi Square statistical test, a p-value of 0.002 was obtained, indicating that there is a significant relationship between soil pollution in the yard by STH and helminthiasis infection in children. This could be caused by factors such as poor personal hygiene and environmental sanitation.